Evaluation of Common Bean (Phaseolus vulgaris L) Germplasm Under Temperate Conditions of Kashmir Valley - D. Debouck2 and A. Graner3, P. A. Sofi1*, M. Y. Zargar1, (Journal of Phytology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Forty two genotypes of Rajmash (41 exotic and one local check) were evaluated in a Randomized block design with two replications for morphological and yield parameters as per the descriptor developed by CIAT and USDA. Most of the accessions were dry pulse type with only one accession being snap type with succulent pods without any fibers. In terms of plant growth about 70% accessions were Indeterminate Bush type and 30% were indeterminate climbing. Similarly, for traits like flower color, pod color, Seed coat pattern & seed size, the accessions were grouped in to two distinct classes, while as more than two classes were observed in case of seed coat color, seed brilliance, seed shape and pod color at maturity. In all these traits, highest frequency was observed in case of use category, pod color & seed coat pattern (97.56%) followed by pod color at maturity (95.20%). Heritability estimates were high for all the traits ranging from 79.472% for seeds/pod to as high as 94.367% in case of days to maturity. Genetic advance was also high in case of most of the traits especially plant height, seed yield, number of pods/plant, leaf area. The analysis correlation coefficients (Table) revealed that grain yield was significantly correlated with number of pods/plant (0.732) followed by 100 seed (0.430), leaf area (0.371), seeds/pod (0.355) and plant height (0.329) but was negatively correlated with days to flowering, days to maturity and pod length.